Recent developments in cell-based assays and stem cell technologies for Botulinum neurotoxin research and drug discovery - Kiris, Erkan (Expert Rev Mol Diagn, 2014)
Botulinum neurotoxins (BoNTs) are exceptionally potent inhibitors of neurotransmission, causing muscle paralysis and respiratory failure associated with the disease botulism. Currently, no drugs are available to counter intracellular BoNT poisoning. To develop effective medical treatments, cell-based assays provide a valuable system to identify novel inhibitors in a time- and cost-efficient manner. Consequently, cell-based systems including immortalized cells, primary neurons, and stem-cell derived neurons have been established. Stem cell-derived neurons are highly sensitive to BoNT intoxication and represent an ideal model to study the biological effects of BoNTs. Robust immunoassays are used to quantify BoNT activity and play a central role during inhibitor screening. In this review, we examine recent progress in physiologically relevant cell-based assays and high-throughput screening approaches for the identification of both direct and indirect BoNT inhibitors.